Optimizing the quality of research in Veterinary Parasitology - Perusso, Cristiane Olier [UNESP]; Nagata, Walter Bertequini [UNESP]; Inácio, Sandra Valéria [UNESP]; Castilho, Gilmara [UNESP]; Ferrari, Alessandro Moreira; Gomes, Jancarlo Ferreira; Bresciani, Katia Denise Saraiva [UNESP] (Elsevier, 2022)
Countless research is carried out until new discoveries are transformed into products or services available to the population. This trajectory can be slower and more costly or even impossible when irreproducible data are obtained in the most diverse fields of science. Thus, quality management appears as an essential tool to guarantee the reliability of academic research results. In this work, we demonstrate the applied strategy to implement a Quality Management System (QMS) in a research laboratory in Veterinary Parasitology and we highlight the adaptable quality requirements in this scientific research environment. For this, the Plan-Do-Check-Act (PDCA) quality tool was used, and two internal audits were performed, one before and one after implementation. The audits reached 67 (41.36%) and 157 (96.91%) points before and after implementation, respectively, with a significant difference between the moments studied. Thus, we demonstrate that the adoption of QMS principles in research is feasible. The methodology applied in this work can be adopted by managers from other laboratories interested in the implementation of quality standards as a support in the reproducibility of research.
Keywords: GLP; ISO/IEC 17025; Quality assurance; Research laboratory